If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3x + -1) + -3(2x) = 1 Reorder the terms: 3(-1 + 3x) + -3(2x) = 1 (-1 * 3 + 3x * 3) + -3(2x) = 1 (-3 + 9x) + -3(2x) = 1 Remove parenthesis around (2x) -3 + 9x + -3 * 2x = 1 Multiply -3 * 2 -3 + 9x + -6x = 1 Combine like terms: 9x + -6x = 3x -3 + 3x = 1 Solving -3 + 3x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 3x = 1 + 3 Combine like terms: -3 + 3 = 0 0 + 3x = 1 + 3 3x = 1 + 3 Combine like terms: 1 + 3 = 4 3x = 4 Divide each side by '3'. x = 1.333333333 Simplifying x = 1.333333333
| 3n+35= | | 0.9x-2.1-0.9=0.2(5-x) | | 0.029x+2=0.034x | | 7(y-6)+3y=10(y+1) | | 11+18=x+19 | | (2/9)g=8 | | 9(4x+1)=10(3x+2) | | 0.029x+2x=0.034x | | 2849=37(p+20) | | f(x)=2t-3whatisf(7) | | -3x+5=-2(3x+5) | | 15+(-5x)=15-5x | | 3y+4=-1y+-4 | | -7u+11=-9(u-1) | | 0.029+2x=0.034x | | 2x(2x-5)(5x+2)=0 | | 8(-9p+2)-7p= | | 814=-22a | | -2(x-7)=-4x+20 | | 5v-89=2v+34 | | 3n+35=7n+35 | | 9w-10=2(w+9) | | 5+x^2=65 | | -2x+5=20-x | | 3x(x+2)=3x^2+4x-3+2x | | -3(5y-2)-y=-2(y-2) | | 23=3u+8 | | 8x-3.4=3x-6.7 | | -8d-d+7d=72 | | (w-4/-9)(-2/-3) | | -5(y-3)=-15 | | -8u+2(u+5)=16 |